Spatial assessment of the availability of healthcare facilities at district level in Balochistan using GIS: identifying gaps and way forward - Ullah, Shafi; Ullah, Niamat; Tariq, Aqil; Panezai, Sanaullah; Tahir, Penha; Khan, Bakhtiar (Spatial information research (Online), 2025)
The availability of healthcare facilities equipped with allied health services is crucial for achieving better health. Balochistan, the largest province of Pakistan by area, faces severe problems in ensuring the availability of healthcare facilities at the district level. This study aims to assess the geospatial analysis of the distribution and availability of healthcare facilities at the district level across Balochistan province. Data from global and national open sources were used to generate maps showing the location of healthcare facilities at the district level across the province. The data on healthcare facilities were collected from the Health Department of the Government of Balochistan. The geospatial analysis was carried out using ArcGIS 10.8.2 software. Additionally, the health care services were overlaid with the district’s population density to measure availability. The findings revealed the categorization of districts as low, medium and high based on the availability of healthcare facilities present in each district concerning population. The findings revealed that the number of hospitals in the districts of Balochistan varies i.e., availability is low in 13 districts, medium in 12 districts and high in 7 districts.